2018
DOI: 10.3389/feart.2018.00019
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tropical Cyclones in Precipitation Over the Tropical and Subtropical North America

Abstract: Tropical cyclones (TCs) are essential elements of the hydrological cycle in tropical and subtropical regions. In the present study, the contribution of TCs to seasonal precipitation around the tropical and subtropical North America is examined. When TC activity over the tropical eastern Pacific (TEP) or the Intra Americas Seas (IAS) is below (abovenormal), regional precipitation may be below (above-normal). However, it is not only the number of TCs what may change seasonal precipitation, but the trajectory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 31 publications
1
63
0
Order By: Relevance
“…Tropical cyclones (TCs) are also important moisture carriers. Arid or semi-arid regions can benefit greatly from a single TC event because one system can produce such intense precipitation (Dominguez and Magaña 2018). TCs are well known for transporting moisture from the tropics to the subtropics and mid-latitudes, but they also can induce drying conditions in regions that are remote to their circulation, approximately more than 500 km (Dominguez and Magaña 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tropical cyclones (TCs) are also important moisture carriers. Arid or semi-arid regions can benefit greatly from a single TC event because one system can produce such intense precipitation (Dominguez and Magaña 2018). TCs are well known for transporting moisture from the tropics to the subtropics and mid-latitudes, but they also can induce drying conditions in regions that are remote to their circulation, approximately more than 500 km (Dominguez and Magaña 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This drying effect has been rarely explored and quantified. It is explained in terms of weak subsidence outside the core of the system that is forced mechanically and may produce clear skies and moisture divergence in neighboring regions to the TC system (Emanuel 1997;Dominguez and Magaña 2018). In other words, while some arid or semi-arid regions are favored by TC occurrence, other distant regions from the TC center can be adversely affected in their accumulated seasonal rainfall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prat and Nelson (2013a) found that near 15% of yearly rainfall over Mexico's Pacific Coast is related to TCs; later, Prat and Nelson (2016) quantified that up to 32% of the precipitation is associated with TCs along the Gulf of Mexico and 50% in southern Baja California; TCs accounted for almost all daily accumulations above 100 mm day −1 over Baja California. Over semiarid regions of Mexico TCs may contribute up to 50% of the seasonal rainfall (Domínguez and Magaña 2018). To complement these previous studies, we analyse the monthly climatology of the contribution of TCs over Middle America, including the effect of TCs on extreme rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of TCs to rainfall in Mexico has been demonstrated on a broad scale (e.g., Englehart and Douglas, 2001;Agustín Breña-Naranjo et al, 2015;Khouakhi et al, 2017;Dominguez and Magaña, 2018). Agustín Breña-Naranjo et al, 2015 found that TCs in Mexico may contribute between 20 and 60% of the observed seasonal rainfall for some coastal regions.…”
Section: Introductionmentioning
confidence: 99%